Molecular Subtyping of Prostate Cancer - Kaffenberger, Samuel D. (Curr Opin Urol, 2016)
PURPOSE OF REVIEW: The recent publication of The Cancer Genome Atlas molecular taxonomy of primary prostate cancer highlights the increased understanding of the genomic basis of human prostate cancer, but also emphasizes the complexity and heterogeneity of prostate cancer. RECENT FINDINGS: 7 molecular subclasses have been defined on the basis of early genomic alterations, which are largely mutually exclusive. SUMMARY: We review the recent advances in the genomic understanding of human prostate cancer, with focus on molecular subclassification. Broadly, prostate cancer can be classified based upon whether specific genomic rearrangements, such as the TMPRSS2-ERG fusion occur or whether specific alterations such as SPOP and FOXA1 mutations occur. The molecular drivers remain to be identified in a further quarter of human prostate cancers. Depending upon the molecular subclassification and the coincident genomic alterations, specific clinical insights can be gained from this information, including associations with pathologic factors, race, and prognosis, as well as the possibility for future precision therapies.